(untitled) (Web of Teachers: Inderscience Research, 2023)
This article explores methods and approaches aimed at adapting the educational process to the individual needs and abilities of students. Issues related to the creation of a favorable educational environment that takes into account different learning styles, individual characteristics and needs of each student are revealed. As a result, the article aims to identify the importance and effectiveness of using adaptive pedagogy in pedagogical universities in order to improve the quality of education and individual success of students